E fez-se a luz: contribuições do medium fotográfico para a instauração do realismo literário - Juchem, Marcelo (Contingentia, 2009)
The nineteenth century was the scene of deep changes in several areas of society: art, industry, science and others. Officially emerged in 1839, the photographic medium was received, discussed and practiced by many of these areas. This article deals with the arisal and the first receptions of photography in the artistic sphere, considering the shock between painting x photography, the discussion about visible reality and its forms of representation in art. It is also briefly discussed the artistic and social context in which the first realisitic publications appeared, the importance of photography in these texts, how they were received in Germany and the fundamental differences between French and German literary realism. Thus, it is intended to point the emergence of the photographic medium as one of the aspects which - through the theoretical and conceptual reconfigurations which have taken place in art - contributed to the establishment of the realistic movement in painting and literature.